Liberal culturalism and multicularity in peru. Reflections from the political theory of will kymlicka - Sánchez Torres, Augusto (2017)
Univocalpublicpoliciesandthesingle-universal citizenship that sponsors the nation-state – always made from a hegemonic culture – can not express the many cultural events and quasi- political identities of peoples and ethnocultural minorities (hence the social conflicts, those who are ready to accrue). Similarly ethnic fundamentalisms illiberal, it is possible that the nation-state with liberal democracy, covertly, hide some also fundamentalist overtones. This essay aims to reflect on the latter assumption and presents some outputs them away. Will Kymlicka Following the “plural State” may be an alternative to meet the multiplicity of existing societies facto deep diversity as Peru. The theory that it takes the name of liberal culturalism.